1978
DOI: 10.1093/ajcn/31.8.1413
|View full text |Cite
|
Sign up to set email alerts
|

Selenium concentration and glutathione peroxidase activity in blood of New Zealand infants and children

Abstract: The blood selenium (Se) concentrations of New Zealand children were lower than those reported for children living in other countries. This low blood Se was primarily determined by the low dietary intake of the children which, in turn, reflects the low Se content of New Zealand soils. Blood Se also varied geographically, with age, and with differences in quantities and types of food eaten. Children with phenylketonuria and maple syrup urine disease on synthetic diets had low Se intakes and blood Se concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 12 publications
3
17
0
1
Order By: Relevance
“…In agreement with earlier reports (4,5,11,12), we found a positive correlation between the plasma selenium level and the GSH-Per activity in red blood cells. The fact that this relationship exists suggests at least a relative selenium deficiency in the infants with low plasma selenium values.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with earlier reports (4,5,11,12), we found a positive correlation between the plasma selenium level and the GSH-Per activity in red blood cells. The fact that this relationship exists suggests at least a relative selenium deficiency in the infants with low plasma selenium values.…”
Section: Discussionsupporting
confidence: 94%
“…In more replete selenium areas, infant levels are less than levels in adults (21)(22)(23). There are limited data suggesting that this is also true in New Zealand (18,24), although no very young infants have been studied and no information is available for premature infants. Before investigating links with BPO, we measured the selenium status and the glutathione peroxidase status of infants admitted to the regional neonatal unit at Christchurch Women's Hospital and studied their relationships to the age of the infants.…”
mentioning
confidence: 99%
“…Selenium deficiency has already been reported in celiac patients (Stazi & Trinti, 2010;Yuce et al, 2004). Several studies have also reported a strong correlation between Gpx activity and Se level in the blood, especially when Se concentration is low (< 80 g/L) (Lloyd et al, 1989;McKenzie at al., 1978). Aw and coworkers suggested that GPx and GR per se are not limited in the catabolism of LOOH in the intestine.…”
Section: Discussionmentioning
confidence: 94%